Salt stress alters the selectivity of mature pecan for the rhizosphere community and its associated functional traits - Shi, Mengting; Qin, Tao; Pu, Zhenyang; Yang, Zhengfu; Lim, Kean-Jin; Yang, Menghua; Wang, Zhengjia (Frontiers in Plant Science, 2025)
IntroductionSalt stress is a major global environmental factor limiting plant growth. Rhizosphere bacteria, recruited from bulk soil, play a pivotal role in enhancing salt stress resistance in herbaceous and crop species. However, whether the rhizosphere bacterial community of a mature tree can respond to salt stress, particularly in saline-alkalitolerant trees, remains unexplored. Pecan (Carya illinoinensis), an important commercially cultivated nut tree, is considered saline-alkali tolerant.MethodsPecan trees (12 years) were subjected to different NaCl concentrations for 12 weeks. Collected samples included bulk soil, rhizosphere soil, roots, leaves, and fruit. Amplicon sequencing data and shotgun metagenomic sequencing data obtained from the samples were investigated: 1) microbial communities in various ecological niches of mature pecan trees; 2) the characteristic of the rhizosphere bacteria community and the associated functional traits when pecan suffered from salt stress.Results and discussionWe characterized the mature pecan-associated microbiome (i.e., fruit, leaf, root, and rhizosphere soil) for the first time. These findings suggest that niche-based processes, such as habitat selection, drive bacterial and fungal community assembly in pecan tissues. Salt stress reduced bacterial diversity, altered community composition, and shifted pecan’s selective pressure on Proteobacteria and Actinobacteria. Shotgun metagenomic sequencing further revealed functional traits of the rhizosphere microbiome in response to salt stress. This study enhances our understanding of mature tree-associated microbiomes and supports the theory that shaping the rhizosphere microbiome may be a strategy for saline-alkali-tolerant mature trees to resist salt stress. These findings provide insights into salt tolerance in mature trees and suggest potential applications, such as the development of bio-inoculants, for managing saline environments in agricultural and ecological contexts.